First Observations on the Re-Established Southeast Florida Recreational Swordfish Tournament Fishery - Levesquee, Juan C.; Kerstetter, David W. (NSUWorks, 2007)
Recreational tournaments for swordfish (Xiphias gladius) existed in the Florida Straits between 1977 and 1983 before disappearing due to low catch rates and an overexploitation of the stock. The first recent swordfish tournament occurred in 2001 off southeast Florida with 13 participating vessels. In 2002, three swordfish tournaments were observed and anglers were interviewed to determine catch and gear characteristics of the re-established recreational fishery. A total of 156 vessels participated in these three tournaments, catching 112 swordfish and hooking an additional 48 animals. The combination of the recovery of the North Atlantic swordfish stock and the continuation of the 2001 closure of the Florida Straits to commercial pelagic longline fishing gear is expected to result in the continued expansion of the southeast Florida recreational swordfish fishery.